2020
DOI: 10.1063/5.0023961
|View full text |Cite
|
Sign up to set email alerts
|

The MHD continuum with a radial electric field

Abstract: The effects of a radial electric field, which is ubiquitous in stellarators, are considered when a system of reduced-MHD equations is derived from a gyro-kinetic Vlasov–Maxwell system. The resulting equations for the MHD continuum have been implemented into the continuum code CONTI. For a tokamak case, the MHD continuum is calculated and compared with a gyro-kinetic continuum calculated using the EUTERPE code, where good agreement of the obtained continua could be shown. Finally, MHD continua including the rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…One can see that the frequency remains at the toroidicity-induced gap for all times of the nonlinear evolution. The shear-Alfvén continuum is computed using the CONTI code [18,19] within the slowsound approximation.…”
Section: Alfvén Eigenmodes In the Presence Of Fast Ions And Electroma...mentioning
confidence: 99%
“…One can see that the frequency remains at the toroidicity-induced gap for all times of the nonlinear evolution. The shear-Alfvén continuum is computed using the CONTI code [18,19] within the slowsound approximation.…”
Section: Alfvén Eigenmodes In the Presence Of Fast Ions And Electroma...mentioning
confidence: 99%
“…Another possibility one may consider is to use a precomputed damping rate γ d (r, ω) that depends on radius and frequency, for instance using a gyrokinetic solver for the plasma dispersion relation, such as LIGKA [63,64]. Moreover, it has been shown that radial electric fields can also have an impact on the structure of Alfvén continua in the frequency range of interest [65] and, thus, may affect chirping dynamics.…”
Section: Appendix D Characterization and Verification Of The Model D1 Background Plasma Responsementioning
confidence: 99%
“…Another possibility one may consider is to use a precomputed damping rate γ d (r, ω) that depends on radius and frequency, for instance using a gyrokinetic solver for the plasma dispersion relation, such as LIGKA [57,58]. Moroever, it has been shown that radial electric fields can also have an impact on the structure of Alfvén continua in the frequency range of interest [59] and, thus, may affect chirping dynamics. The condition dG/dt = 0 underlying our implementation of the δ f method, namely Eq.…”
Section: C4 Ghost Chirps and Resonance Overlapmentioning
confidence: 99%